2001
DOI: 10.1148/radiol.2211001412
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Cerebral Infarction in the Middle Cerebral Arterial Territory: Deep Watershed versus Territorial Subtypes on Diffusion-weighted MR Images

Abstract: The evolution time of ADC is faster for TI than for WI. This difference, which likely originates from the different pathophysiologic and hemodynamic features of the two infarction types, might account for the relatively large range of ADC values reported for the time course of ischemic strokes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 28 publications
(52 reference statements)
8
37
1
Order By: Relevance
“…These graphs and earlier studies [5][6][7][8][9]13,14 indicated a diŠerence between evolution of water diŠusion in an early phase (from one hour to a few days from onset) and subsequent evolution. The simplest model that accounts for the biphasic evolution will be a linearlinear (LL) model with 4 parameters ( p1, p2, p3, t0): p1(t-t0)+p2, 1 hÃtÃt0; p3(t-t0)+p2, t0ºtÃ1600 h. As a next simplest model, we considered an exponential-linear (EL) model with 5 parameters ( p1, p2, p3, p4, t0): p1+p2 exp (-p4t), 1 hÃtÃt0; p3 (t -t0)+p1+p2 exp (-p4t0), t0ºtÃ1600 h. In these models, the time of transition, t0, and the rate constant, p4, were assumed to be common in the L/Cs of ADC¿, ADC¥, and <ADC>.…”
Section: Regression Analysissupporting
confidence: 75%
See 2 more Smart Citations
“…These graphs and earlier studies [5][6][7][8][9]13,14 indicated a diŠerence between evolution of water diŠusion in an early phase (from one hour to a few days from onset) and subsequent evolution. The simplest model that accounts for the biphasic evolution will be a linearlinear (LL) model with 4 parameters ( p1, p2, p3, t0): p1(t-t0)+p2, 1 hÃtÃt0; p3(t-t0)+p2, t0ºtÃ1600 h. As a next simplest model, we considered an exponential-linear (EL) model with 5 parameters ( p1, p2, p3, p4, t0): p1+p2 exp (-p4t), 1 hÃtÃt0; p3 (t -t0)+p1+p2 exp (-p4t0), t0ºtÃ1600 h. In these models, the time of transition, t0, and the rate constant, p4, were assumed to be common in the L/Cs of ADC¿, ADC¥, and <ADC>.…”
Section: Regression Analysissupporting
confidence: 75%
“…Systematic investigation of the temporal evolution of water <ADC> in human white matter early after stroke onset 7,8,13 has shown that <ADC> averaged across patients remains consistently low one through 4 days after initial reduction and begins to increase and that temporal evolution is slower for white matter than for gray. The ADC has been shown to decrease rapidly within one hour from onset of ischemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought that slower ischemic tissue repair is the best explanation. 2,3,[6][7][8] In a serial MRI study of small cortical and lacunar ischemic lesions, two of 21 lesions showed high DWI signals with an ADC below normal 54-144 days after infarction onset.…”
Section: )mentioning
confidence: 99%
“…Subsequently, the hyperintensity seen on DWI is related to the increment in the T2 relaxation time (the T2 shine-through effect). 4,9) Persistent cases of DWI hyperintensity combined with hypointensity on the ADC map during the subacute to chronic stage of infarction have been demonstrated in some studies, 2,3,[6][7][8] mainly in cases of minor stroke that involved the cerebral white matter. We present a patient with complete right middle cerebral artery (MCA) infarction showing persistent hyperintensity on DWI and hypointensity on the ADC map for over 8 months.…”
Section: Introductionmentioning
confidence: 98%